1

Løs likningen



1)   6x - 6 = - 6 + 7x   

 2)   5x - 4 = - 26 + 3x   

3)   4x - 2 = 7x - 23 

 4)   7x + 6 = 2x + 16 

5)    - 4 - 2x = 2x + 44  

 6)   4x + 9 = 2x - 7  

7)   6x - 9 = - 6x + 3

 8)   5x - 9 = 2x + 0 

9)    - 2x + 9 = 97 + 6x

 10)   - x + 4 = 0 + 3x 




2

Løs likningen



1)   7x - 2 = 22 - 5x   

 2)   2x + 5 = - x + 32 

3)    - 5 - 3x = - 4x + 7 

 4)   x - 2 = - 50 - 5x

5)   x - 3 = 4x - 36

 6)   x - 10 = - 6x + 53 

7)   7 + 4x = - 7x - 70

 8)   7x + 3 = 93 - 3x

9)   6x + 7 = 5x + 14 

 10)    - 4x + 2 = 8 - 2x




3

Løs likningene



1)   3 - 2x + x = - 2  

2)   10 - 2x + 6x = 14

3)   x - 3 + 7x = 5

4)    - 3x - 1 + 4x = 1 

5)   16 = 5x - 2x + 10

 6)    - 2 + 4x + x = - 7  

7)   7x + 3 + 5x = 39  

 8)    - 8 - x + 3x = - 8 

9)   54 = 5x + 4x - 9

10)    - 38 = - 6x - 7x + 1 




4

Løs likningene



1)    - 80 = 5x + 3x - 8  

 2)   3x + 6 + 3x = 60   

3)    - 4x - 10 + 7x = 2

 4)   x + 6 + 2x = 0   

5)    - 2x + 6 + 3x = 15  

 6)   7x + 5 + 2x = 95  

7)   x + 3 + 5x = - 39

 8)   2x + 10 + 7x = - 8 

9)    - 9 + 2x + 2x = - 5 

 10)    - 2x + 4 + x = 7




5

Løs disse likningene



1)   4x + 10 = - 3x + 10 

2)    - 5x - 10 = - 22 - x 

3)   5x - 5 = 76 - 4x

4)   2x + 8 = - 76 - 5x

5)   10 + 6x = 5x + 13 

6)    - 6x + 1 = - 119 + 6x  

7)    - 5x + 7 = - 23 - 2x 

8)   6x + 3 = 23 + 4x

9)   2x - 4 = - 37 + 5x

10)    - 7x + 8 = 2x - 19